Tough Love: The Effects of Debt Contract Design on Firms’ Performance - Spyridopoulos, Ioannis (The Review of Corporate Finance Studies, 2020)
Abstract I investigate whether restrictive loan covenants disrupt or improve firms’ operating performance. Using an instrumental variables approach to address the endogenous relationship between covenant strictness and firms’ efficiency, I find that stricter loan covenants lead to an increase in profitability and firm value even when firms do not violate a covenant. Stricter covenants improve performance only in firms with managerial agency conflicts: those without large shareholder ownership, facing softer competition in their product market, or with weaker shareholder rights. The evidence suggests that by designing stringent contracts ex ante, creditors create positive externalities in poorly governed firms through managerial incentives. Received December 7, 2018; editorial decision May 31, 2019 by Editor Uday Rajan. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.